Derivation and analysis of a system modeling the chemotactic movement of hematopoietic stem cells - Kettemann, Anita; Neuss-Radu, Maria (Journal of Mathematical Biology, 2008)
It has been shown that hematopoietic stem cells migrate in vitro and in vivo following the gradient of a chemotactic factor produced by stroma cells. In this paper, a quantitative model for this process is presented. The model consists of chemotaxis equations coupled with an ordinary differential equation on the boundary of the domain and subjected to nonlinear boundary conditions. The existence and uniqueness of a local solution is proved and the model is simulated numerically. It turns out that for adequate parameter ranges, the qualitative behavior of the stem cells observed in the experiment is in good agreement with the numerical results. Our investigations represent a first step in the process of elucidating the mechanism underlying the homing of hematopoietic stem cells quantitativel
Keywords: Chemotaxis equations; Homing; Hematopoietic stem cells; Nonlinear boundary conditions